Author survey data about bibliometrics and altmetrics for open access monographs – including data about online usage and citations of academic books from Stockholm University Press - Sofie Wennström; Gabor Schubert; Jeroen Sondervan; Graham Stone (Stockholm University, 2019)
This dataset includes a file with results from a survey sent to authors of open access monographs. The survey was available during March–April 2019 and the results are analysed in a paper presented at the 2019 Elpub conference on Jun 2–4 in Marseille, France entitled 'The significant difference in impact – an exploratory study about the meaning and value of metrics for open access monographs'.
Version 2 of the dataset has been updated with the slides presented at the conference and the link to the full paper published in the French open archive HAL.

The respondents of the survey were asked to comment on assumptions about bibliometrics and altmetrics currently in practice, and to think about the meaning of such data in relation to their experiences as authors of books published in a digital format and with an open license (i.e. a creative commons license). The survey questionnaire is included as a separate text document.
The dataset also includes measures about the usage of open access books published by Stockholm University Press, including information about online usage, mentions in social media and citations. This data is collected from the publisher's platform, the Altmetric.com database, and citation data was collected from Dimensions, Google Scholar, Web of Science and CrossRef. The data was collected in February 2019, except for the figures from the OAPEN Library database, which was collected in November 2018.
The paper, including the analysis of these data, is to be published in the Elpub Digital Library. The tables included in the dataset may vary slightly from those in the published paper, due to space restraints in the published version.
Keywords: Library and Information Studies; Information Studies; Biblioteks- och informationsvetenskap